(untitled) (GIST – Education and Learning Research Journal, 2021)
Study abroad experience (SA) has been regarded as one of the best ways to enhance English language proficiency because it offers opportunities for learners to experience the use of English in real instances. The present study attempted to explore the language development of a group of EFL learners participating in Erasmus program for SA experience where English is not used as L1. To achieve this, the data were collected through three instruments; Language Contact Profile (LCP), Then and Now Survey, and semi-structured interviews. Fifty-nine students answered LCP and Then and Now self-assessment and eight students were interviewed. The quantitative result revealed that students experienced greater gains in their oral skills. On the other hand, qualitative results confirm the greater gains in speaking skills with respect to other skills. Moreover, the results highlighted the significance of the learning context and the quality and quantity of interaction for language development.